Prediction of body weight from body dimensions in Karadi sheep - Karim, Goran Mohammad; Karym, Chnoor Mhamad (Sulaimani Journal for Pure and Applied Sciences, 2018)
Animal live body weight is an important feature, but can seldom be measured in rural areas due to lack of reasonable accurate scales. Hence, farmers have to rely on questionable estimates of the body weights of their sheep, leading to inaccuracies in decision making. The primary method of weighing animals without scale is to regress body weight to body characteristics, which can be measured readily. Experiment was carried out on 100 males and 100 females of Karadi sheep at 12 months of age, Data for body weight and linear body measurements were taken at traditional private sheep farms in Sharazoor-Halabja, Kurdistan region-Iraq. Result of Body weight (BW) of males and females were 38.98±0.68 and 37.53±0.75 kg, respectively. Body length of males and females were 68.83±0.28 and 67.49 ± 0.32 cm, respectively. Moreover, heart girth of males and females were 89.63 ± 0.27 and 87.98 ± 0.25 cm, respectively. Furthermore, height at wither of males and females were 64.71± 0.30 and 67.53 ± 0.18 cm, respectively. Chest width of males and females were 17.49 ± 0.07 and 16.81± 0.07 cm, respectively. While chest depth of males and females were 30.19 ± 0.11 and 29.66 ± 0.11 cm, respectively. It was observed that based on the result of the optimum multiple regression equation of predictive body weight of male Karadi sheep (Minimum C(p) and highest R2 values) the proposed equation is as follows: = 1.431 body length + 1.0107 heart girth + 0.050 height at wither + 0.312 chest width - 0.137 chest depth - 154.727 Similarly, the optimum multiple regression equation of predictive body weight of female Karadi sheep (low C(p) and highest R2 values) the proposed equation is as follows: = 0.974 body length + 0.232 heart girth + 0.366 height at wither + 2.678 chest width + 1.331 chest depth - 158.005
Keywords: Karadi sheep,body weight,body dimensions,correlation and regression